NILAI-NILAI KESETARAAN RAS DALAM AL-QUR’AN (KAJIAN ATAS TAFSIR AL-MISBAH) - Huda, Nurul; Islamiyah, Wildatul (JURNAL ISLAM NUSANTARA, 2021)
The purpose of this study is to describe verses related to the values of racial equality, which should be used as "objects" to find out and analyze racial equality in Indonesia. However, many people reject it. The emergence of this rejection has sparked the birth of this article so that the values of racial equality in QS are later known. Al-Hujurat: 13 perspectives on Al-Misbah's interpretation. This study uses a qualitative method with the type of verse analysis research from thematic interpretation by interpreting verses related to the values of racial equality. The results of the study show that, First, a difference in race, language, skin color, nation, and other differences is proof of Allah SWT's power in creation. Second, the Qur'an surah Al-Hujurat verse 13 rejects an attitude of racism as a prohibition on boasting of one's people or group, thus demeaning others. Third, the implication of the interpretation of the Qur'an surah Al-Hujurat verse 13 is that humans must respect the differences that Allah SWT has outlined.